PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS X RPL.1 SMK NEGERI 1 TAPEN: SMK NEGERI 1 TAPEN BONDOWOSO - BUDI SANTOSO (Dewan Pendidikan Bondowoso, 2021)
The purpose of this action research is to improve the physics learning outcomes of students of class X RPL.1 Vocational High School 1 Tapen through the application of the problem base learning model. The research used by the author in this study is Classroom Action Research (CAR). Classroom action research is part of action research, and research at this level is part of qualitative research. Referring to these characteristics classroom action research can be defined as an action research carried out by teachers as well as researchers in the classroom or together with others (collaboration) through activities to design, implement and reflect on collaborative and participatory actions aimed at improving or improving the quality of the learning process in the classroom through a certain action in a cycle. This research was carried out at Vocational High School Negeri 1 Tapen which is located at Jalan Kawan Ijen no 99 Jurangsapi, Tapen District, Bondowoso Regency. The research was carried out for 3 months, from September 2018 to November 2018. The subjects of this study were students of class X RPL.1 Vocational High School Negeri 1 Tapen in the Odd Semester of the 2018/2019 Academic Year, totaling 35 students. The object of this research is the implementation of learning Physics subjects on the material elasticity properties of materials using the PBL learning model The data analysis technique used in this research is descriptive qualitative. The data obtained from the observations are reduced by selecting important data and discarding useless information. Furthermore, the data that has been reduced is presented in a certain pattern to make it easier to read. The last step is to conclude the data by selecting important information without including unimportant information. From the implementation of the research starting from the pre-cycle, cycle I and cycle II, it can be concluded that the use of the Problem Based Learning learning model can improve the learning outcomes of Physics students in class X RPL.1 Vocational High School Negeri1 Tapen, in this case it can be seen from the following research data: ). Learning completeness, in the pre-cycle student learning completeness was 45.71%, in the first cycle it increased to 68.57%, while in the second cycle it increased to 82.86%. 2). The absorption of students, in the pre-cycle the absorption of students was 63.43%, in the first cycle it increased to 69.86%, while in the second cycle it increased to 78.86%.